X linked agammaglobulinaemia and rheumatoid arthritis. Issue 7 (25th November 2004) - Verbruggen, G; De Backer, S; Deforce, D; Demetter, P; Cuvelier, C; Veys, E; Elewaut, D
Abstract : Background: Much interest has been shown recently in the pathogenic role of B cells in rheumatoid arthritis (RA) owing to the marked clinical responses to anti-CD20 treatment in RA. Case report: A patient with X linked agammaglobulinaemia (XLA) presented with an erosive symmetric polyarthritis with histological features of RA, including formation of a destructive pannus. Furthermore, the patient developed subcutaneous nodules that were histologically indistinguishable from rheumatoid nodules. Surprisingly, lymphocytic infiltrates in both the synovium and nodule consisted almost exclusively of CD8 + T cells. Discussion: Although some peculiar B cell subsets have been described in patients with XLA, no B cell subsets could be demonstrated in synovial tissue or the subcutaneous nodule. This case illustrates that classical RA can develop in the absence of mature B cells.